Relative Efficiency of Small and Medium Scale Agribusiness Enterprises in Imo State, Nigeria. - Emeka , Emesowum Charles; A, Mbanasor Jude (Asian Journal of Agriculture and Rural Development, 2013)
The study examined the Relative Efficiency of Small and Medium Scale Agribusiness Enterprises in Imo state, Nigeria using the stochastic translog profit function approach. A multi-stage and simple random sampling technique were used in selecting four hundred eighty enterprises (240 each from small and medium scale) from two Agricultural Zones of the state namely Orlu and Owerri zones. Economic efficiency was analysed using the stochastic translog profit function and Maximum Likelihood Estimation (MLE) technique was employed to estimate the function. Full economic efficiency was tested using generalized Likelihood Ratio (LR) and t-test statistic was employed to compare the small and medium scale enterprises in the area. The result depicted that both enterprises were not efficient but small scale enterprise was more efficient than medium scale enterprise. There was no significant difference in mean efficiency between the small and medium scale enterprises. The economic efficiencies of the enterprises varied widely between 0.09 and 0.93 and 0.08 and 0.91 respectively for small and medium scale enterprises with a mean of 0.57 and 0.54. Access to credit and business experience was found influencing economic efficiency in both small scale and medium scale enterprises. The study observed that there was an opportunity for increase in enterprises’ efficiency and small and medium scale enterprises should focus more on ways of accessing credit facilities.